2013
DOI: 10.1111/liv.12144
|View full text |Cite
|
Sign up to set email alerts
|

Transarterial embolization as neo‐adjuvant therapy pretransplantation in patients with hepatocellular carcinoma

Abstract: Pre-transplant TAE with the more permanently occluding PVA particles significantly reduces post-transplant HCC recurrence in patients within the Milan criteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
43
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 27 publications
1
43
0
2
Order By: Relevance
“…13 Pretransplant locoregional therapies (LRTs) including transarterial modalities (transarterial chemoembolization-TACE, transarterial radioembolization-TARE) and percutaneous thermal ablative strategies (radio frequency ablation, microwave ablation) have been widely adopted by transplant programs to bridge and/or downstage HCC recipients before LT. LRT mediates its effect by achieving pathologic tumor necrosis, with reported rates of complete pathologic response (cPR) in 27% to 57% of patients after TACE 14,15 and 47% to 75% after thermal ablation (TA). [16][17][18] Although LRT has been shown to mitigate the risks of tumor progression and waitlist dropout, [16][17][18][19][20] data regarding its effectiveness in reducing posttransplant HCC recurrence 21,22 and improving posttransplant survival 23 are limited and sometimes contradictory. 24,25 The current study describes the largest single-center experience of LT in HCC recipients undergoing pretransplant LRT, many of whom received multimodality treatment.…”
mentioning
confidence: 98%
“…13 Pretransplant locoregional therapies (LRTs) including transarterial modalities (transarterial chemoembolization-TACE, transarterial radioembolization-TARE) and percutaneous thermal ablative strategies (radio frequency ablation, microwave ablation) have been widely adopted by transplant programs to bridge and/or downstage HCC recipients before LT. LRT mediates its effect by achieving pathologic tumor necrosis, with reported rates of complete pathologic response (cPR) in 27% to 57% of patients after TACE 14,15 and 47% to 75% after thermal ablation (TA). [16][17][18] Although LRT has been shown to mitigate the risks of tumor progression and waitlist dropout, [16][17][18][19][20] data regarding its effectiveness in reducing posttransplant HCC recurrence 21,22 and improving posttransplant survival 23 are limited and sometimes contradictory. 24,25 The current study describes the largest single-center experience of LT in HCC recipients undergoing pretransplant LRT, many of whom received multimodality treatment.…”
mentioning
confidence: 98%
“…Given the low quality of evidence currently available, it is imperative that we better understand the impact of bridging therapy on patients with HCC. previous reports where the use of LRT, more specifically TA(C)E, was independently associated with lower incidence of post-transplant HCC recurrence (10). The reported rates of RFS in patients who received LRT was comparable to those who did not at 1, 3, and 5-years (89%, 77%, 68% vs. 85%, 75%, 68%, p=0.490).…”
mentioning
confidence: 61%
“…It has been used as bridge treatment for a number of years, and several studies have already demonstrated its effectiveness. An analysis done in the larger series indicated that 27% to 57% of the patients within MC had complete necrosis of the treated lesion 17,18 . Patients with a reduction of at least 30% in tumor size until complete devascularization .…”
Section: Discussionmentioning
confidence: 99%